Entering Higher Professional Education: Unveiling First-Year Students’ Key Academic Experiences and Their Occurrence Over Time - Willems, Jonas; Coertjens, Liesje; Donche, Vincent (Frontiers in Psychology, 2021)
To date, little understanding exists of how first-year students in professionally oriented higher-education (HE) programs (i.e., those that provide vocational education to prepare students for a particular occupation) experience their academic transition process. In the present study, we first argued how the constructs of academic adjustment and academic integration can provide complementary perspectives on the academic transition of first-year students in (professional) HE. Next, we examined what first-year students in professional HE contexts perceive to be the most important experiences associated with their academic transition process in the first semester of their first year of higher education (FYHE). To this end, we adopted the fundamentals of the critical incident technique and asked 104 students in a Flemish (Dutch-speaking part of Belgium) university college (which offers professional HE programs, such as nursing) to complete ‘reflective logs’ with open questions at the start of the second semester of their FYHE, wherein they reflected on three critical academic experiences during their first semester. An inductive, cross-case content analysis of the collected narratives showed that students reported on nine themes of academic experiences, which relate to five adjustment themes (dealing with the organization of the study program, organizing study work, committing to the study, following class and taking notes, and processing learning content outside class) and four integration themes (feeling competent, feeling stressed, feeling prepared, and feeling supported). Further analyses showed that although some of the nine themes of academic experiences appear to be more important at different times in the first semester, they all seem to be meaningful throughout the whole semester.